Introduction to the Book and the Round Table Review. Karma Ben-Johanan’s "Jacob’s Younger Brother: Christian-Jewish Relations after Vatican II" - D'Costa, Gavin (Studies in Christian-Jewish Relations, 2023)
No abstract is available.